Seasonal variation of intestinal Trichuris sp. in sheep and goats from Maharashtra State - Padwal, Nitin; Humbe, Atul; Jadhav, Swati; Borde, S N (International Multidisciplinary Research Journal, 2011)
The present paper deals with the seasonal variation of Trichuris sp. of sheep and goats. The high prevalence of Trichuris sp. are recorded in the month of December 2008 and November 2009 i.e. 82.8% and 85.0% respectively followed by in the month of March 2009 and February 2010 i.e. 60% and 70% respectively where as low prevalence are recorded in the month of August 2008 and July 2009 i.e. 50% and 31.5% respectively.Â